2013
DOI: 10.1371/journal.pone.0077037
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Diet Withdrawal Leads to an Initial Plaque Instability and Subsequent Regression of Accelerated Iliac Artery Atherosclerosis in Rabbits

Abstract: Effect of long term cholesterol diet withdrawal on accelerated atherosclerosis in iliac artery of New Zealand White (NZW) rabbits has not been explored so far. Atherosclerosis was thus induced in rabbits by a combination of balloon injury and atherogenic diet (AD) (1% cholesterol and 6% peanut oil) feeding for 8 weeks (baseline) followed by chow diet (CD) feeding for 4, 8, 16, 32, 50 and 64 weeks. The plaque characterization was done using histology, real time RT-PCR and vasoreactivity studies. Significant ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…Quantitative gene expression analysis was performed using SYBR Green as described previously65. Briefly, total RNA was extracted using TRIZOL reagent, and cDNA was synthesized using RevertAid H Minus first strand cDNA synthesis kit.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative gene expression analysis was performed using SYBR Green as described previously65. Briefly, total RNA was extracted using TRIZOL reagent, and cDNA was synthesized using RevertAid H Minus first strand cDNA synthesis kit.…”
Section: Methodsmentioning
confidence: 99%
“…Macrophages activated by cholesterol play a very important role in inducing steatohepatitis or arteriosclerosis (in the form of foam cells) (Khanna et al. ). Many studies have shown that cholesterol significantly increases the levels of serum leptin, interleukin‐6, fibrosis, and liver alpha‐smooth muscle actin ( α ‐SMA) in mice fed a solid diet containing 0.2% cholesterol with 30% fat, and that dysregulated hepatic cholesterol homeostasis as well as accumulation of liver free cholesterol are involved in the pathogenesis of NAFLD/NASH (Arguello et al.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry for macrophage was adopted from our previous work and Khanna' research [10,32]. Firstly, paraffin-embedded aortas were segmented into 4 mm slices at 5 mm intervals, dewaxed and rehydrated.…”
Section: Immunohistochemistry For Macrophagementioning
confidence: 99%